Gaya Kepemimpinan Karismatik Abu Bakar Ash-Shiddiq Perspektif Kitab Al-Bidayah wan Nihayah dan Relevansinya pada Pendidikan Tinggi Islam - Hammam Misbakhul Munir; Rz. Ricky Satria Wiranata (Al-fahim : Jurnal Manajemen Pendidikan Islam, 2024)
Islamic education in Indonesia is faced with inadequate quality and quantity of teachers, as well as very low educational effectiveness. This can hinder the achievement of educational goals. Leadership is one of the factors that determine the success of educational programs. A leader's leadership style refers to his traits, knowledge, skills, and problem-solving abilities. This research is qualitative, with a library research method, which aims to find out the characteristics of Abu Bakar Ash-Shiddiq's charismatic leadership listed in the book Al-Bidayah wan Nihayah and find out whether these characteristics have relevance to leadership in Islamic higher education. The subject of this research is the head of the Islamic Education Management  study program (MPI) at STAI Terpadu Yogyakarta. Data were collected using interview and documentation techniques, and the validity of the data was tested using triangulation techniques. The results of the study state that the book Al-Bidayah wan Nihayah explains the leadership characteristics of Abu Bakar Ash-Shiddiq which are shown through wise, fair and not favoritism, determined and firm, as well as caring and compassion. These characteristics are relevant to the leadership style of the head of MPI STAI Terpadu Yogyakarta.